Perception of health risks in Lao market vendors. (19th August 2020) - Philavong, Chanfong; Pruvot, Mathieu; Reinharz, Daniel; Mayxay, Mayfong; Khammavong, Kongsy; Milavong, Phonesavanh; Rattanavong, Sayapeth; Horwood, Paul F.; Dussart, Philippe; Douangngeun, Bounlom; Theppangna, Watthana; Fine, Amanda E.; et al.
Abstract: Wet markets are a critical part of South‐East Asian culture and economy. However, their role in circulation and transmission of both endemic and emerging disease is a source of concern in a region considered a hotspot of disease emergence. In the Lao People's Democratic Republic (Lao PDR, Laos), live and dead wild animals are frequently found in wet markets, despite legislation against the bushmeat trade. This is generally considered to increase the risk of disease transmission and emergence, although whether or not wildlife vendors themselves have indeed increased incidence of zoonotic disease has rarely been assessed. In preparation for a future longitudinal study of market vendors investigating vendors' exposure to zoonotic pathogens, we conducted a pilot survey of Lao market vendors of wildlife meat, livestock meat and vegetables, to identify demographic characteristics and potential control groups within markets. We also investigated baseline risk perception for infectious diseases among market vendors and assessed the association between risk perception and risk mitigation behaviours. The surveys conducted with 177 vendors revealed similar age, sex, ethnic background and geographical origin between vendor types, but differences in professional background and work history for livestock meat vendors. The perception of disease risk was very low across all vendors, as was the reported use of personal protective equipment, and the two appeared unrelated. Personal risk discounting and assumptions about transmission routes may explain this lack of association. This information will help inform the development of future research, risk communication and risk mitigation policy, especially in the light of the COVID‐19 pandemic.